Students’ Perception on Multimedia Used by the Teacher during Online Learning Activity in SMA Pembangunan Laboratorium UNP - Ika Haya Aulia; Fitrawati Fitrawati (Universitas Negeri Padang, 2021)
This research was motivated by the condition this time. The teachers start to use multimedia to teach the students in the distance learning process during the Covid-19 pandemic. This study aims to determine the perception of SMA Pembangunan Laboratorium UNP towards multimedia in English learning online. This research was a descriptive study using a quantitative approach with the data collection technique using a questionnaire. The sample in this study was 87 students of SMA Pembangunan Laboratorium UNP. The data analysis technique used descriptive analysis was stated in the form of a percentage. The result showed the students' perception of SMA Pembangunan Laboratorium UNP towards multimedia in learning English online. In detail, as many as; 8 students (9.20%) had very less positive perceptions, 17 students (19.54%) had less positive perceptions, 27 students (31.03%) had quite positive perceptions, 35 students (40, 23%) had positive perceptions, and no students had very positive perceptions. The highest frequency is 40.23%, which is in the positive category. Thus the students’ perception of the use of multimedia in learning English online at SMA Pembangunan Laboratorium UNP was positive.